Optimising individual stance position in the swim start on the OSB11 - Kibele, A.; Biel, K.; Fischer, S. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The aim of this study was to evaluate systematic variations of the preferred stance of elite swimmers in relation to their swim start performance on the OSB11. Variations of the preferred stance were examined regarding the front leg (left vs. right), the centre of mass height (low vs. high), the stance width (narrow vs. wide), and a rear vs. a front weighted stance. Two thirds of the subjects displayed either improvements or no changes in swim start performances through stance variations of their preferred stance configuration. For half of the subjects, at least one stance alternative provided a better swim start time than the preferred stance. The average improvements in the swim start performance were found to be 0,06s with extreme values as large as 0,14s. The majority of the swim start improvements were associated with a front weighted stance, a decreased foot distance and an elevated centre of mass position. For this stance configuration, shorter block times were observed. In this regard, it is assumed that short block times are essential for the swim start performance on the OSBll.